Exploring cultural competence through the 'humans of Malaysia project - Marof, Aini Azeqa (Human Resource Management Academic Research Society, 2023)
The field of High Impact Education Practices (HIEPs) advocates the use of Community-based Learning (CBL), an immersive pedagogical method that has shown promising results. This project investigates the practical application of CBL within a Social Psychology course, facilitated through the innovative "Humans of Malaysia Project." In this venture, students were required to integrate with various communities, adopting roles as amateur street photographers. This experiential learning method provided students with a platform to apply essential social psychology concepts such as intergroup relations, contact theory, attribution, and attitude change in authentic, real-world environments. The strategic application of structured interviews and the sharing of experiences via social media platforms enhanced students' understanding of underprivileged communities. The process served to bridge the existing divide between the theoretical teachings of academia and the reality of the general public by creating a holistic learning experience. One noteworthy outcome of this project was the significant elicitation of empathy from the students, and a consequent reduction in prejudice and stereotypes towards unfamiliar social groups. This fostered interpersonal skills, cultural competence, and a heightened sense of social responsibility among the participants. The project also yielded direct, impactful results in the form of funds raised for individuals encountered during the interviews, demonstrating the tangible social impact of this teaching strategy. In conclusion, the implementation of CBL through the "Humans of Malaysia Project" showcased the transformative potential of experiential learning methods. The project played an instrumental role in shaping students' attitudes and fostering community connections, thereby establishing CBL as a valuable and effective strategy within HIEPs.